Teaching jazz history: disrupting gendered narratives - Burke, Robert Louis; Hall, Clare; Kellett, Michael J.; Luebbers, Johannes (Frontiers in Education, 2024)
The teaching of jazz history in tertiary institutions has historically focussed on the “great men” of jazz (Whyton, 2010), with jazz historiography giving scant recognition to female-identifying musicians (Rustin and Tucker, 2008). The historicising of certain individuals and their music is fundamental to understanding jazz, yet it silences female and gender non-binary voices, overshadowing the roles they played in the evolution of the genre. This study aims to deepen our understanding of the experience of students engaging with jazz history in the 21st century. Halberstam and Halberstam’s (2005) theory of queer time and disruption serves as the primary framework for analysing shifts in teaching and learning perceptions concerning hegemonic and male-dominated narratives in jazz history. To understand the experiences and perspectives of those directly involved in jazz history pedagogy this research draws on an education-focused, polyethnographic approach utilising data derived from self-selected student research topics, student surveys, and teacher interviews. Our findings highlight both the shifting discourse within tertiary education, teaching experiences and the interwoven attitudes of students, reflecting on how these dialogues came to impact and shape the other. The study provides implications for how jazz education may continue to evolve in both attitude and enlightened access in the education of jazz learners. The objective of this paper’s outcomes is to inform the translation of more diversified narratives in tertiary jazz pedagogy and music education more broadly.